Pelaksanaan Jaminan Fidusia Di Masa Pandemi Covid-19 - Moenandar, Revandio Hendruno; Akyuwen, Rory Jeff; Kuahaty, Sarah Selfina (Faculty of Law, Universitas Pattimura, 2021)
Introduction: The case of Credit Agreement and Debt Recognition with a fiduciary guarantee that occurred between Roberth Gomies as a debtor and PT. Sinar Mas Multifinance (PT. SMMF) as a creditor with a guarantee of 1 (one) unit of Public Transport Vehicle. In this case, the payment made by Robert Gomies experienced a payment delay due to the corona virus outbreak 19. So the vehicle used as credit collateral in the fiduciary agreement was forcibly/unilaterally withdrawn without the knowledge and permission of the debtor.Purposes of the Research: Knowing and Reviewing Forms of Protection for Fiduciary Guarantees in the Covid 19 Pandemic Period and Execution Mechanisms for Fiduciary Guarantees in the Covid 19 Pandemic Period. Methods of the Research: The method used is normative legal research. The research approach is a statutory approach and a conceptual approach. Sources of legal materials used are primary legal materials, secondary legal materials, and tertiary legal materials. The technique of collecting legal materials is through literature study and then analyzed through a perspective using qualitative methods.Results of the Research: The results of the study show that the procedure for withdrawing the object of fiduciary security must refer to the Regulation of the National Police Chief Number 8 of 2011 which is carried out by the creditor or his proxies must submit a request for securing the execution of the withdrawal of the fiduciary object which is made in writing addressed to the local police chief by attaching the following conditions: the following conditions, a. a copy of the fiduciary guarantee deed, b. a copy of the fiduciary guarantee certificate, c. A warning letter to the debtor to fulfill his obligations. d. The identity of the executor of the execution, e. Executioner's assignment letter. In addition, the Constitutional Court Decision Number 18/PUU-XVII/2019 has also provided legal certainty for fiduciary guarantee.